DIGITAL TRANSFORMATION OF COMMUNICATION CHANNELS FOR INTERACTION WITH STAKEHOLDERS IN THE INDUSTRY 4.0 ENVIRONMENT - Nekhoroshkova, Yulia; Khramova, Karyna (Socio-economic relations in the digital society, 2023)
The article examines communication channels for interaction with stakeholders, highlights trends in their digitalization, and explores effective methods of managing communication channels considering the peculiarities of conducting business during Industry 4.0. It provides an overview of technology transformation throughout different stages of human development and its impact on the economy and business. The concept of Industry 4.0 is discussed, along with a characterization of the changes brought by the Fourth Industrial Revolution. The concept of stakeholders is explained, their types are identified, and a general characterization is provided. The stages of interaction with stakeholders, including engagement, persuasion, service, and partnership, are described, and optimal channels with elements of digitalization for content dissemination at each stage of interaction are identified. The study explores key trends in the digitalization of marketing communication channels with stakeholders.